A Review of Teaching Factory Implementation Strategies within Culinary Vocational Education - indarsih, fitria retno; Wicaksono, Nurzahra Fathiyanabila; Remania, Vanessa (Program Studi Pendidikan Vokasi Seni Kuliner, 2026)
The Teaching Factory (TeFa) is an industry-integrated pedagogical framework aimed at bridging the gap between vocational education and workforce requirements. In culinary arts vocational programs, TeFa implementation is vital for enhancing student competencies through contextualized learning within simulated professional environments. This study investigates the concepts, implementation models, benefits, and strategic challenges of TeFa in the culinary sector via a comprehensive literature review. Employing a qualitative descriptive method, the research analyzes academic literature, journal articles, and relevant policy documents. The results indicate that TeFa significantly improves work-readiness and strengthens both technical and soft skills. However, its success is often constrained by inadequate facilities, curriculum gaps, and limited industry synergy. This study serves as a conceptual reference for the advancement of production-based learning in culinary vocational education.